Reinventing Soccer Communication through Sportainment with Genzers in Spain: The case of the Kings League - Carrero Márquez, Oliver; García Muñoz, César; García Chamizo, Fernando (VISUAL REVIEW. International Visual Culture Review / Revista Internacional de Cultura Visual, 2024)
This study explores the Kings League's impact on sports communication and its appeal to Generation Z in Spain, contrasting it with traditional football leagues. The Kings League's "sportainment" approach, blending sport and entertainment with innovative digital broadcasting, resonates with young audiences. Key elements include its spontaneity, spectacle, and the involvement of charismatic figures. The research underscores the need for new formats and sports communication methods to engage younger generations, highlighting the importance of personalization, immediacy, and innovation in sports to maintain cultural relevance and audience engagement.